Preferred explosives for blasting in the presence of combustible custs - M. J. Sapko; E. S. Weiss; R. W. Watson (Canadian Institute of Mining, Metallurgy and Petroleum, 1988)
The relative incerdivity of several blasting agents was evaluated in the Bureau's Bruceton Experimental Mine (BEM) . The minimum charge weights resulting in the ignition of predispersed oil shale dust clouds were measured for each of the explosives. A 400 g unstennned charge of ANFO (ammonium nitrate-fuel oil) was sufficient to initiate an oil shale dust explosion, whereas a 1000 g unstenuned charge of an emulsion blend did not ignite the dust even with the addition of 4% methane gas. Several stenuning materials were evaluated in the BEM for their effectiveness in preventing the ignition of near stoichiometric methane-air mixtures. Water stenuning was superior to all other inhibitors tested against methane. Explosibility testing of fine sulfide ore dust in a 20 L chamber and in the BEM show that the dust is capable of propagating an explosion given nominal concentrations of 700 to 800 g/m3. Results are encouraging and irrlicate that there is merit in pursuing explosive composition as a means of reducing ignition probability of oil shale and sulfide dust clouds generated during nonnal blasting operations. The proper selection of explosives and stenuning materials should significantly reduce the probability of secondacy dust explosions in oil shale and sulfide ore mining.